2019
DOI: 10.33309/2639-8281.020106
|View full text |Cite
|
Sign up to set email alerts
|

The Rule Of “10’s” in the Management of Unilateral Cleft Lip Children: The Komfo Anokye Teaching Hospital Experience

Abstract: Background: Despite significant advances in cleft lip and palate (CLP) care, the often quoted "rule of 10 s" has not been objectively investigated concerning its practicality since its inception, especially, in low-resourced country like Ghana. Aim of the Study: This was to evaluate the unilateral cleft lip weight, haemoglobin and surgical repair outcome by considering the "Rule of 10's". Materials and Methods: A retrospective study of all consecutive patients who presented with unilateral cleft lip and were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…In a retrospective study in Ghana, it was found that children with unilateral CL/P and unilateral complete cleft lip had lower hemoglobin and weight compared to unilateral incomplete cleft lip patients (Acheampong et al, 2019). Additionally, when repairs were performed in anemic and malnourished children, there were higher infection rates (Acheampong et al, 2019). The results highlight the need for improved studies of the outcome of preoperative screening factors when providing cleft care in SSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study in Ghana, it was found that children with unilateral CL/P and unilateral complete cleft lip had lower hemoglobin and weight compared to unilateral incomplete cleft lip patients (Acheampong et al, 2019). Additionally, when repairs were performed in anemic and malnourished children, there were higher infection rates (Acheampong et al, 2019). The results highlight the need for improved studies of the outcome of preoperative screening factors when providing cleft care in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this rule has not been properly studied in low resource settings within SSA. In a retrospective study in Ghana, it was found that children with unilateral CL/P and unilateral complete cleft lip had lower hemoglobin and weight compared to unilateral incomplete cleft lip patients (Acheampong et al, 2019). Additionally, when repairs were performed in anemic and malnourished children, there were higher infection rates (Acheampong et al, 2019).…”
Section: Clinical Practice Patternsmentioning
confidence: 99%
“…The hospital commenced partnership with the Smile Train in 2007 and has been providing free cleft care to patients with clefts. The rule of 10 as proposed by Wilhelmsen and Musgrave [4] and modified by Millard [8] is used for guiding scheduling of our patients for primary lip repair. The data of patients who received cleft care are entered into the Smile Train Express (STX).…”
Section: Study Design and Settingmentioning
confidence: 99%
“…One of the common guidelines for the timing of surgical cleft lip repair is the rule of ten (4). Although its validity is questioned, the “rule of ten” guideline is still widely used(6–8). By this rule, children who are ten weeks old, attained the weight of five kilograms and have a haemoglobin of 10g/dl can commence primary lip repair if there are no other mitigating medical conditions (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation